2015
DOI: 10.3389/fvets.2015.00057
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Intestinal Barrier Function by Host Defense Peptides

Abstract: Intestinal barrier function is achieved primarily through regulating the synthesis of mucins and tight junction (TJ) proteins, which are critical for maintaining optimal gut health and animal performance. An aberrant expression of TJ proteins results in increased paracellular permeability, leading to intestinal and systemic disorders. As an essential component of innate immunity, host defense peptides (HDPs) play a critical role in mucosal defense. Besides broad-spectrum antimicrobial activities, HDPs promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 155 publications
(260 reference statements)
3
106
0
2
Order By: Relevance
“…It is plausible that entinostat, through HDAC inhibition, can reverse V. cholerae-induced disruption of intestinal tight junctions and consequently decrease gut permeability. On the other hand, recent studies have reported that host defense peptides play roles in intestinal barrier function by directly regulating mucin and tight-junction protein expression (37). Cathelicidin-BF, a peptide purified from the venom of the Bungarus fasciatus snake, has been shown to ameliorate lipopolysaccharide (LPS)-induced disruption of the epithelial barrier in rats via prevention of the downregulation of tight-junction proteins (38).…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that entinostat, through HDAC inhibition, can reverse V. cholerae-induced disruption of intestinal tight junctions and consequently decrease gut permeability. On the other hand, recent studies have reported that host defense peptides play roles in intestinal barrier function by directly regulating mucin and tight-junction protein expression (37). Cathelicidin-BF, a peptide purified from the venom of the Bungarus fasciatus snake, has been shown to ameliorate lipopolysaccharide (LPS)-induced disruption of the epithelial barrier in rats via prevention of the downregulation of tight-junction proteins (38).…”
Section: Discussionmentioning
confidence: 99%
“…AMPs have a defensive role, but their function cannot be distinguished from those of nutrient acquisition. For example, it has been shown that feeding AMPs to livestock improves nutrient digestibility, intestinal morphology and growth performance [122]. Ultimately, as has been noted elsewhere [33], activities of immune detection and response resemble nutrient breakdown, uptake, and transport, and as the examples above suggest, immune pathways in Drosophila appear to be regulating multiple aspects of host metabolism.…”
Section: Expanding Functions For Amps: Beyond Traditional Immune Rolesmentioning
confidence: 98%
“…Благодаря многочисленным исследованиям у дефенсинов выявлен широкий диапазон эффектов в регули-ровании иммунитета человека (рис. 2) [14,94,171,245].…”
Section: происхождение и структура дефенCинов млекопитающихunclassified
“…Иммунозащитные пептиды, синтезируясь в клетках кожи в местах потен-циального проникновения микробов, обеспечивают растворимый барьер, который действует как прегра-да для инфекций [39,40]. Если кожа не повреждена, то рост бактерий контролируется бактериостатиче-скими и бактерицидными соединениями, такими как псориазин и РНКаза 7 [171]. Однако при поврежде-нии или инфицировании кожи экспрессия иммуно-защитных пептидов повышается посредством уве-личения их синтеза кератиноцитами и секреции при дегрануляции рекрутированных нейтрофилов.…”
Section: дефенсины -как элемент взаимодействия с факторами гемостазаunclassified